Efficient copper-catalyzed Sonogashira coupling reactions and simulation studies. Issue 12 (18th June 2017) - Ali, Imran; Nighot, Dnyaneshwar; Lone, Mohammad Nadeem; Jain, Arvind
ABSTRACT: A practical copper-catalyzed I-substitutions of alkyl-2-iodobenzoates with alkynes have been developed using Cu powder as a catalyst under solvent, cocatalyst, and base-free conditions. This reaction system is new, facile, efficient, and economical that gives Sonogashira coupling products in excellent yields (up to97% ). The coupled products (A–J ) were characterized by CHNS, 1 H NMR, and 13 C NMR and are found soluble in ethyl acetate and dichloromethane. In addition, simulation studies ofA–J were performed with aspulvinone dimethylallyltransferase enzyme and observe good binding affinity. The reported compounds may act as anti-cizmatics, anti-fobic in future and also have the inhibition of aspulvinone dimethylallyltransferase properties to control Alzheimer's, Schizophrenia, etc. diseases. GRAPHICAL ABSTRACT: